Desain Pembelajaran Model Assure Pada Materi Al-Quran Hadits Berbasis Video Untuk Meningkatkan Minat Belajar Peserta Didik - Khoirun Niswatin; Husniyatus Salamah Zainiyati; Rudi Al Hana; Abdulloh Hamid (LP2M IAIN kUDUS, 2021)
The purpose of this study was to describe the video-based ASSURE model learning on Al-Qur'an Hadith material in madrasas. In this study, the method used is R&D (Research and Development). The background of using this model is as a solution to the needs of students for innovative learning in this pandemic era, where students must be able to explore and master the material using the internet technology in online learning. For this reason, an educator is required to have competence in designing effective learning models to support the right teaching and learning process. ASSURE is a simple learning design that can be used to create an effective, efficient, and interesting learning so that it is very relevant to use for students at the Ibtidaiyah Madrasah level. The result of the study showed that there was a significant change in the increase in student interest in learning between before and after using learning video media. At the pre-test stage, the achievement of learning outcomes was only 68, but at the post-test stage it increased to 81. Thus, the ASSURE learning model based on video learning was very effective in increasing the learning interest of madrasah ibtidaiyah students.